How do Children Choose Toys and are These Choices Associated with Developmental Outcomes? - Мargarita N. Gavrilova; Vera L. Sukhikh (Lomonosov Moscow State University, 2024)
Background. Despite the depth of theoretical analysis of play activity there is a lack of empirical data on the choice of toys by modern children. A toy is a means of constructing play and, therefore, can largely influence its key characteristics. Objectives. The study is a continuation of an earlier series of works aimed at experimentally clarifying children's toy preferences and the relationship of these preferences to individual developmental performance. Study Participants. 202 children aged 4-5 years were participants in the study. Previously published data obtained on a sample of 3-4-year-old children were used to analyze the age dynamics in toy preference. Methods. The study used an experimental design with a multiple-choice forced-choice method. Diagnostics of children's mental development included assessment of the main components of regulatory functions and the ability to understand emotions and was performed using instruments standardised on a Russian sample. Results. It was shown that children prefer highly realistic and detailed toys. In particular, such factors as the toy being detailed, the possibility of its use in playing through familiar plots, the adequacy of role-playing actions with it and the possibility to endow it with human features proved to be fundamentally important for children. Conclusions. From the distribution of choices in experimental trials and children's verbal explanations, it can be confidently concluded that play activity is based on the laws described in the works of Vygotsky, Elkonin, and Smirnova. It is also shown that children who choose the most realistic toys have better verbal working memory, but have a weaker ability in cognitive flexibility. According to the obtained data, as children grow older, they tend to choose less anthropomorphic toys.